The Dundaga Orthodox Congregation in the Northern Courland (1918–1940): a Short Overview - Ērglis, Dzintars (Acta humanitarica academiae Saulensis, 2025)
In the studies on the socio-political and economic history of Latvia in the 20th century the Dundaga region of the Northern Courland (Northern Kurzeme or Ziemeļkurzeme) is represented quite purely and sporadically. There is a lack of wide, archival-based studies on Dundaga in the 20th century and, moreover, activities of the local Orthodox parish. This article is one of attempts to fill this gap, and it outlines a life of the Dundaga St. Constantine and Elena (Helena) Orthodox parish in the interwar period (1918–1940).Major challenges of this small parish were long-standing unresolved real estate ownership case and numerous litigations associated with it, as well as problems of finding a priest, who would reside permanently in Dundaga.Thanks to a happy coincidence, the real estate belonging to the Dundaga Orthodox parish did not face destruction during World War I. However, it was the reason why for more than 10 years the parish was forced to engage in many lawsuits defending its property rights. The real estate ownership dispute occurred between the Dundaga congregation and heirs of Erasts Valters, a wealthy Orthodox landowner from Arlava (Ārlava) parish, Talsi District, who built a complex of clerical buildings for the Dundaga parish on the plot of land purchased by it in March, 1908, from the local Baron Christian von der Osten-Sacken. When E. Valters died in 1919, his daughter, son-in-law and grandson tried to take advantage on the situation and benefit significantly from the original deal made by the Consistory and their deceased relative.After coup d’état of May 15, 1934, the state intensified its efforts to gain greater control over the activities of the religious denominations, and the Orthodox parish of Dundaga also had to accept new realities of life under authoritarian rule, but their actual influence on day by day activities of the congregation was not overwhelming.Only in 1936, the parish of Dundaga had overcome all major difficulties: obtained its own priest, solved the issue of real estate ownership, as well as made major repairs to the church and set up a new bell. For the first time in the interwar period, it was able to embark on a stable and full-fledged religious life, which, unfortunately, lasted only four years – until the fateful events of 1940.
Keywords: Latvian Orthodox Church; parish of St. Constantine and Elena (Helena) in Dundaga; the District of Dundaga; Northern Courland (Northern Kurzeme, Ziemeļkurzeme)